2016
DOI: 10.1111/age.12507
|View full text |Cite
|
Sign up to set email alerts
|

Using RNA‐Seq SNP data to reveal potential causal mutations related to pig production traits and RNA editing

Abstract: RNA-Seq technology is widely used in quantitative gene expression studies and identification of non-annotated transcripts. However this technology also can be used for polymorphism detection and RNA editing in transcribed regions in an efficient and cost-effective way. This study used SNP data from an RNA-Seq assay to identify genes and mutations underlying production trait variations in an experimental pig population. The hypothalamic and hepatic transcriptomes of nine extreme animals for growth and fatness f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 69 publications
0
21
1
Order By: Relevance
“…RNA-Seq data obtained from liver, hypothalamus and Longissimus dorsi muscle samples, from pigs with divergent phenotypes for growth and fatness on each backcross [ 43 , 44 ] was used for SNP calling, in order to identify candidate polymorphism within the selected candidate genes. RNA-Seq data filtering, mapping and SNP calling was carried out with CLC Genomics Workbench ( www.clcbio.com ).…”
Section: Methodsmentioning
confidence: 99%
“…RNA-Seq data obtained from liver, hypothalamus and Longissimus dorsi muscle samples, from pigs with divergent phenotypes for growth and fatness on each backcross [ 43 , 44 ] was used for SNP calling, in order to identify candidate polymorphism within the selected candidate genes. RNA-Seq data filtering, mapping and SNP calling was carried out with CLC Genomics Workbench ( www.clcbio.com ).…”
Section: Methodsmentioning
confidence: 99%
“…As costs for whole-genome sequencing become more affordable, sequence variability at the whole-genome level is becoming an alternative to positional or physiological candidate gene approach. As an alternative to whole-genome sequencing, sequence variation information can also be retrieved from RNA-seq experiments and linked to expression levels [85]. The big limitation, and a severe bottleneck, still is how to perform large-scale functional tests on the SNP/INDEL/CNV mutations resulting from these experiments, particularly in non-coding regions.…”
Section: The Molecular Basis Of Imf Content and Compositionmentioning
confidence: 99%
“…Therefore, this phenomenon leads to differences between the final transcript sequence and the DNA region it was transcribed from [ 4 ]. Since its discovery in 1986 in trypanosomes [ 5 ], RNA editing has been reported to occur in a broad range of species ranging from bacteria [ 6 ] to mammals [ 7 , 8 ]. As inosines are read as guanosine by the translation and splicing machineries [ 4 , 9 ], RNA editing can influence alternative splicing [ 10 ], recoding of open reading frames [ 4 ] and can affect miRNA-regulated post-transcriptional gene silencing [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Novel RNA-editing sites can be discovered by direct comparison between cDNA sequences and their corresponding genomic position. Several recent next generation sequencing (NGS) based studies, have reported RNA editing sites in different vertebrates including human [ 8 , 12 , 14 ], mouse [ 16 ], pig [ 17 ], chicken [ 18 ] and bovine [ 19 ]. There are several challenges for identifying RNA editome using RNA-Seq data including the discrimination of true RNA editing sites from single-nucleotide polymorphisms (SNPs), somatic mutations, systematic sequencing errors and mapping errors [ 20 ].…”
Section: Introductionmentioning
confidence: 99%